Aplikasi Sistem Informasi Geografis (SIG) Pemetaan Lahan Pertanian dan Komoditas Hasil Panen Di Kabupaten Sidrap Berbasis Web - Masnur, Masnur; Alam, Syahirun; Muhammad, Ihsar (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
One of the regencies in Indonesia, whose people are mainly engaged in agriculture is Sidrap (Sidenreng Rappang). However, it is still difficult to monitor and report agricultural products and production by relying on telephone and sms only to send information on agricultural products and production results due to the difficulty of users understanding the computerized systems provided such as using Microsoft Excel and Microsoft Word which are still difficult for some users, then the data sent only in the form of messages that are intended upon arrival to the relevant agency. Based on the above background, this study aims to create an Web-based Geographical Information System. This research method uses field research methods (Field Research) and literature review (Literature Study). The results of this study are a Web-Based Geographical Information System (GIS) Mapping Agricultural Land and Commodities Application in Sidrap Regency, namely this application can make it easier to handle the process of agricultural data collection and production results, with monitoring system data collection and data validation reported by the admin (extension officer).